GREEN ATMOSPHERICS AND CUSTOMER WELL-BEING TO CUSTOMER SATISFACTION AND REVISIT INTENTION IN CITY HOTEL SECTOR SURABAYA - Dewi, Hayuning Purnama (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This study aims to analyse the role of green atmospherics and customer well-being on customer satisfaction and revisit intention at the City Hotel sector of Surabaya. The sample was selected using purposive sampling based on three criteria: guests/visitors who visited more than twice, over 25 years old and stayed more than two days. Over six months, 300 questionnaires were distributed to guests and visitors of hotels in central Surabaya, classified as part of the City Hotel sector of Surabaya. The results showed that about 87% or 261 questionnaires were returned and used for analysis. The research was conducted using Structural Equation Modeling (SEM). The findings indicate that green atmospherics and customer well-being positively and significantly influence customer satisfaction in the City Hotel Sector of Surabaya. Furthermore, green atmospherics and customer well-being positively influence the revisit intention in this sector.JEL: E24, E220, I25, I140.